Perception and features of luxury clothing in Classical and Hellenistic Greece - Karatas, A.M. Sara (Journal of Greek Archaeology, 2025)
The present paper aims to assess literary sources and temple inventories to give an overview of what made a cloth luxurious. Since the prices for all kinds of clothes and fabrics in ancient Greece are unknown, iconographic and written sources, as well as textile fibres, colours, and decorations, will be considered to determine the types of garments whose manufacturing was costly. Different factors contributed to the expense of clothing production in antiquity, including the type of textile fibres, the complexity of weaving techniques, the dyes, and the level of decoration and embellishment. The temple inventories, alongside literary and iconographic sources, represent an essential corpus for studying luxury clothing in Classical and Hellenistic Greece. Temple inventories record, among others, garment dedications made to various deities. The temple inventories serve as tangible evidence of the types of clothing considered valuable and worthy of dedication to the gods. The iconographic sources, such as vase paintings, sculptures, and reliefs, depict individuals wearing various garments, ranging from simple to elaborate attire. These visual representations offer a rich and diverse view of the styles, colours, and adornments favoured by wealthy people and trends in ancient Greek clothing.